Training for Optimal Sports Performance and Health - Nobari, Hadi; Fuentes García, Juan Pedro (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
In this book, the emphasis is on various training interventions. Types of exercises that can help improve performance in athletes and health in people facing poor movement diseases.Also, we have presented a variety of strength training interventions in the form of various types of research. On the other hand, we continue to monitor internal and external loads related to non-contact injuries and performance analysis.